The Types of businesses mainly pursued by Women-Owned SMEs in Mashonaland West Province of Zimbabwe. - Comfort Zvırıkuzhe; Tasara Majoni; Betserai G .Mashiri (Cita Konsultindo Research Center, 2023)
Women-owned SMEs come in a variety of forms. They can be categorized based on factors including education, motivation, age, corporate traits, and gender. The category of women owned Small and Medium Enterprises (SMEs), which is one of the fastest growing, needs attention for a number of reasons. In many countries, the potential of women who make up half of humanity is sadly underutilised. But it is undeniable that women are vital to many aspects of society, including the local economy. Women are frequently able to break down customary barriers by creating Women-owned SMEs. In many economies, Women-owned SMEs currently make up an increasing proportion of all new businesses. The study focused on establishing typologies of businesses mainly pursued by women-owned SMEs in Mashonaland West Province of Zimbabwe. Pragmatism research philosophy, mixed research approach, cross sectional survey design, structured questionnaires and interviews were employed in this study. The study targeted women SMEs who have been receiving microfinance services in Mashonaland West Province of Zimbabwe. Three hundred and seventy seven women SMEs were exposed to the questionnaire and 30 were exposed to interviews. Descriptive statistics such as mean and standard deviation were used for data analysis. The study findings showed that most women were into the manufacturing business followed by retail, wholesale and agriculture. These findings add something new to the body of existing knowledge. The government is argued to intervene so that MFIs would charge reasonable rates and also MFIs to provide the appropriate products that helps women-owned SMEs to develop. Finally, it is suggested that similar research be conducted with MFIs management and employers as responders. This could result in fresh contributions to the study.